Analisis Pengaruh Customer Intimacy, Ambient Conditional Dan Interactional Justice Terhadap Kepuasan Serta Dampaknya Pada Loyalitas Nasabah - Ika Setiansye; Agung Guritno (Al-bank: Journal of Islamic Banking and Finance, 2023)
The purpose of this study was to determine the effect of Customer Intimacy, Ambient Conditional and Interactional Justice on Customer Satisfaction and its impact on Customer Loyalty of Bank Syariah Indonesia KCP Kebumen. The research method uses a quantitative approach. The population in this study were customers of Bank Syariah Indonesia KCP Kebumen with a sample size of 100 customers. The analysis technique uses path analysis. The results showed that partially Customer Intimacy, Ambient Conditions and Interactional Justice had an effect on customer satisfaction. Customer Intimacy and interactional justice have a direct effect on loyalty through the satisfaction variable. Ambient Condition only has a direct effect on customer loyalty.